Lactobacillus acidophilus potentiates oncolytic virotherapy through modulating gut microbiota homeostasis in hepatocellular carcinoma - Jiayu Zhang; Jinneng Yang; Jinyan Luo; Weili Wu; Haidan Luo; Wenxia Wei; Haimei Lyu; Yuzhi Wang; Hairong Yi; Yijing Zhang; Zongmin Fan; Haiwen Lyu; et al. (Nature Communications)
Abstract Oncolytic viruses (OVs) hold promise for cancer treatment. However, the antitumor efficacy is limited. Microbiota plays a pivotal role in cancer treatment and its impact on oncolytic virotherapy is unknown. Here, we show that VSVΔ51 has higher antitumor efficacy for hepatocellular carcinoma in the absence of microbiota in female mouse models. VSVΔ51 infection causes microbiota dysbiosis, increasing most of the gut bacteria abundance, while decreasing the commensal Lactobacillus. VSVΔ51 reduced intestinal expression of SLC20A1 that binds to Lactobacillus acidophilus (L. acidophilus) CdpA cell wall protein through IL6-JAK-STAT3 signaling, thereby attenuating attachment and colonization of L. acidophilus. L. acidophilus supplementation confers sensitivity to VSVΔ51 through restoring gut barrier integrity and microbiota homeostasis destroyed by VSVΔ51. In this work, we show that targeting microbiota homostasis holds substantial potential in improving therapeutic outcomes of oncolytic virotherapy.